PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP KELALAIAN PENGEMBANG DALAM PRA KEPEMILIKAN RUMAH SANGAT SEDERHANA DI KOTA PAYAKUMBUH - Faisal Buchari (STIH Putri Maharaja, 2018)
Home is one of the basic human needs for shelter. For that the construction of houses and settlements continue to be increased at affordable prices, especially by the low-income community. Consumers have paid a down payment and have made the addition of home building, but after more than 9 (nine) years running signing the credit agreement agreement with the bank that will provide mortgage facilities has not been realized. So the opportunity for consumers to have a home to be delayed can even be closed at all. This research was an analytical descriptive that describes the overall symptoms and legal aspects of consumer protection in the pre sale house purchase agreement is very simple. The data obtained in the analysis and interpreted logically and systematically by using a qualitative juridical approach. The results of field research indicated that there is no consumer protection in the pre-sale agreement to buy a very simple house on Bumi Ngalau Indah housing consumers. Where the consumers who have paid the advance position in the eyes of the same law with consumers who have made a perfect sale and purchase agreement. Based on the results of this study it is advisable that receipts as receipts for advance payment in the prerecord of sale and purchase of houses are very simple to mention about what rights and obligations between consumers and developers, or the addition of other clauses so that consumers are not always on the weak side.